Am Rad der Geschichte drehen : Die Aktion "Verwüstung" des MfS gegen die Bundesrepublik - Bonenkamp, Daniel R. (Studies on the History of Totalitarianism, 2022)
Did the Federal Republic of Germany plan another European border revision just 20 years after the end of the Second World War? Did the plan call for the use of biological and chemical weapons? Bonenkamp's ground-breaking research shows how disinformation campaigns were part of the German-German conflict during the Cold War. One such attempt by East Berlin to internationally discredit its Western class enemy was the Ministry for State Security operation named Aktion 'Verwüstung' (English: operation 'Devastation'), which is the focus of this book. This campaign shows how hard those responsible in the GDR tried to attain international recognition and what enormous resources were mobilised for this. The study is based on numerous original documents